ANALYSIS OF HUMAN RESOUCE PLACEMENT BASED ON ABILITY AND WORK SKILLS USING THE PROFILE MATCHING METHOD - Sumiyatun; Faizal, Edi; Wasiati, Hera (University Of Technology Yogyakarta, 2019)
Human resource management is closely related to employee performance to provide the best service to companies and steak holders. The right placement is a way to optimize the ability, skills towards good work performance for the workers themselves. The right position will be able to help the company (organization) in achieving its goals. Analysis of decision support systems developed in this research uses the Profile Matching method. Criteria for placement of employee positions based on aspects of personality and aspects of work attitude. The results of this research are an analysis used to rank employee competencies that will occupy employee positions in the public relations and admissions departments.